STRATEGI PENGEMBANGAN WISATA BAHARI PANTAI MALALAYANG, KOTA MANADO, SULAWESI UTARA - Fitridamayanti ., Razak; Benu Olfie L. Suzana; Gene H. M. Kapantow (Sam Ratulangi University, 2017)
This study aims to formulate the development strategy of Malalayang Coastal Tourism of Manado City. This research uses descriptive method where data are collected, analyzed and descripted by using qualitative approach. Qualitative approach describes the responses of respondents to marine tourism based on the given questionnaire. Data collection conducted through field observation, interview and literature study. The results of this study indicate that the strategy of marine tourism development Malalayang Beach lies in the position of quadrant I or lies between external opportunities and internal strength. Strategy of maritime tourism development Malalayang Beach Manado City is to maintain and preserve the surrounding environment, the need for the development of facilities and facilities of tourism objects, the rearrangement of â€œsabua buluâ€ as a culinary place and the need for management of the government and private sector to be more focused and run well and both The parties agreed to cooperate to develop sustainable tourism Malalayang Coastal..